2019
DOI: 10.1038/s41581-019-0119-6
|View full text |Cite|
|
Sign up to set email alerts
|

Pre-eclampsia: pathogenesis, novel diagnostics and therapies

Abstract: Pre-eclampsia is a complication of pregnancy that is associated with substantial maternal and fetal morbidity and mortality. The disease presents with new-onset hypertension and often proteinuria in the mother, which can progress to multi-organ dysfunction, including hepatic, renal and cerebral disease, if the fetus and placenta are not delivered. Maternal endothelial dysfunction due to circulating factors of fetal origin from the placenta is a hallmark of pre-eclampsia. Risk factors for the disease include ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
630
2
26

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 746 publications
(756 citation statements)
references
References 254 publications
18
630
2
26
Order By: Relevance
“…In contrast, we observed a significant decrease in the pro-inflammatory cytokine profile in LEW dams throughout pregnancy that is associated with better reproductive outcomes. 22,24 Other studies have observed a significant interaction of HP genotype with recurrent miscarriage and pre-eclampsia. [17][18][19] HP is an anti-oxidant protein that binds free hemoglobin and is therefore increased during inflammation or decreased in the presence of hemolysis.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…In contrast, we observed a significant decrease in the pro-inflammatory cytokine profile in LEW dams throughout pregnancy that is associated with better reproductive outcomes. 22,24 Other studies have observed a significant interaction of HP genotype with recurrent miscarriage and pre-eclampsia. [17][18][19] HP is an anti-oxidant protein that binds free hemoglobin and is therefore increased during inflammation or decreased in the presence of hemolysis.…”
Section: Discussionmentioning
confidence: 97%
“…[20][21][22] This is of great importance because obesity can induce additional physiological and gene dysregulation. 22,24 Other studies have observed a significant interaction of HP genotype with recurrent miscarriage and pre-eclampsia. 24,25 The plasticity of HP could explain the different results in various human proteomic studies where pre-eclampsia or recurrent miscarriage has been associated with either increased or decreased HP and HBB.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Currently, PE is considered to be a multisystem syndrome of human gestation and is related to high maternal and infant morbidity and mortality rates . Pregnancy predisposes females to a higher risk of pulmonary oedema, hepatic and renal failure, seizures, cerebral haemorrhage and even death . Additionally, PE can impact the overall health and well‐being of the foetus.…”
Section: Introductionmentioning
confidence: 99%